Coordinated governance in global value chains: supranational dynamics and the role of the International Labour Organization*. Issue 2 (4th March 2017) - Posthuma, Anne; Rossi, Arianna
ABSTRACT: This article focuses on the role of international organisations (IOs), at the supranational level, in advancing 'coordinated governance' – the interaction and complementary efforts of different public, private and social stakeholders – in promoting labour standards compliance in global value chains (GVCs). While scholars have questioned the ability of IOs to address economic and social challenges posed by globalisation, recent experience of the International Labour Organization (ILO) illustrates how supranational governance can mediate between national and international governance of labour standards in cross-border production systems such as GVCs. Briefly examining three cases reveals concrete dimensions in which the ILO is applying its structure and normative framework to create new configurations of coordinated governance and leveraging its convening power to promote social upgrading in national and GVCs: (1) The Protocol on Forced Labour (2014), which strengthens and updates existing ILO core conventions and promotes cross-border cooperation between states; (2) the ILO's response in the aftermath of the Rana Plaza tragedy in April 2013, convening public and private stakeholders at the national and international levels and (3) the Better Work Programme, a partnership between the ILO and the International Finance Corporation, that involves tripartite participation at the national and global levels.